Peran Budaya Organisasi dalam Meningkatkan Kinerja Pegawai pada Kantor BUMDesMA Lembaga Keuangan Daerah (LKD) Kajang Lako Emas Kecamatan Muara Tembesi Kabupaten Batang Hari - Siti Marlina AZ; Ratna Ratna; Rts. Hartha Delima; Nadiatul Khoiroh; Raden Hebat Kurnia (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The purpose of this study was to determine the role of organizational culture in improving employee performance at the Village-Owned Enterprise (BUMDesMa) LKD Kajang Lako Emas office, Muara Tembesi District, Batang Hari Regency. The analysis method used was quantitative, utilizing simple linear regression analysis. The results found that organizational culture variables influence employee performance. The role of organizational culture in improving employee performance at the Village-Owned Enterprise (BUMDesMa) LKD Kajang Lako Emas office, Muara Tembesi District, Batang Hari Regency, was 63.1%, with 36.9% contributed by other variables not examined in this study.